Crowns’ unions and representative assemblies: notes on the opening speeches of the Portuguese Cortes of 1581 and the English parliament of 1604: Uniões de Coroas e assembleias representativas: notas sobre os discursos de abertura das Cortes portuguesas de 1581 e do Parlamento inglês de 1604 (Revista de História da UEG (REVHIST), 2021)
The Portuguese Cortes and the English Parliament were representative assemblies of great importance throughout the Early Modern age. From 1581, Philip II of Spain ruled the kingdom of Portugal, and in 1603, James VI of Scotland inherited the English throne. Both Philip II and James VI summoned the representative assemblies of their new kingdoms as soon as they could, and in the opening sessions of the Portuguese Cortes and the English Parliament, they ordered, as did Philip II, composed and read, as did James VI, the opening speeches. The speeches delivered at the opening sessions of Early Modern representative assemblies, often witnessed by the monarchs, were very important for the political communities. In this article I investigate the specificities between the speeches read in the opening sessions of the Portuguese Cortes of 1581 and the English Parliament of 1604, namely those parts that deal with the new political unions in question, which took place after the ascensions of Philip II in Portugal and James VI in England.Keywords: Philip II of Spain. James VI of Scotland. Portuguese Cortes. English Parliament.